Users' music information needs and behaviors: Design implications for music information retrieval systems. (7th April 2015) - Lee, Jin Ha; Cho, Hyerim; Kim, Yea‐Seul
Abstract : User studies in the music information retrieval (MIR) domain tend to be exploratory and qualitative in nature, involving a small number of users, which makes it difficult to derive broader implications for system design. In order to fill this gap, we conducted a large‐scale user survey questioning various aspects of people's music information needs and behaviors. In particular, we investigated if general music users' needs and behaviors have significantly changed over time by comparing our current survey results with a similar survey conducted in 2004. In this paper, we present the key findings from the survey data and discuss 4 emergent themes—(a) the shift in access and use of personal music collections; (b) the growing need for tools to support collaborative music seeking, listening, and sharing; (c) the importance of "visual" music experiences; and (d) the need for ontologies for providing rich contextual information. We conclude by making specific recommendations for improving the design of MIR systems and services.